Axl-Targeted Delivery of the Oncosuppressor miR-137 in Non-small-Cell Lung Cancer - Silvia Nuzzo; Silvia Catuogno; Maria Capuozzo; Alfonso Fiorelli; Piotr Swiderski; Serena Boccella; Filomena de Nigris; Carla Lucia Esposito (Molecular Therapy: Nucleic Acids, 2019)
Non-small-cell lung cancer (NSCLC) accounts for 85%–90% of all cases of lung cancer that is the most deadly type of cancer. Despite advances in chemotherapy and radiotherapy, severe side effects and frequent drug resistance limit the success of the treatments, and the identification of new therapeutic options still represents a crucial challenge. Here, we provide the evidence for the therapeutic potential of an aptamer-microRNA (miR) complex (AmiC) composed by an aptamer (GL21.T), able to bind and antagonize the oncogenic receptor Axl, and the miR-137, downregulated in lung cancer and involved in cell survival and proliferation. We found that, when applied to Axl-expressing NSCLC cancer cells, the complex is effectively internalized, increasing miR cellular levels and downregulating miR targets. Most importantly, the complex combines the inhibitory function of the GL21.T aptamer and miR-137, leading to a negative impact on NSCLC migration and growth. The described AmiC thus represents a promising tool for the development of new therapeutic approaches for NSCLC. Keywords: aptamers, miRNAs, NSCLC, targeted delivery